2006
DOI: 10.1108/00070700610661321
|View full text |Cite
|
Sign up to set email alerts
|

Management accounting practices in the British food and drinks industry

Abstract: Acknowledgement:The authors would like to thank the two anonymous reviewers and participants at the EIASM conference on new directions in management accounting: innovations in practice and research (Brussels December 2002) for their valuable comments on earlier drafts of this paper. Financial support from the Chartered Institute of Management Accountants is acknowledged with gratitude. ABSTRACTPurpose -This paper investigates and reports on the management accounting practices in the British food and drinks ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
130
4
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(161 citation statements)
references
References 59 publications
(49 reference statements)
17
130
4
10
Order By: Relevance
“…Phadoongsitthi (2003) in Thailand supported the view by Joshi (2001) by stating that the reasons for such similarities of low adoption of newly developed management accounting practices between Thai and India is because both countries have cultural similarities like large power distance and low individualism group and both countries facing similar problems like the lack of training and expertise. Research in developed countries (see, for example, Chenhall & Smith, 1998;Pierce & O'Dea, 1998;Abdel-Kader & Luther, 2006), although reporting an increasing usage of modern management accounting practices, agreed that basic or traditional management accounting practices are still dominant in most firms. It is argued that high acceptance of traditional techniques may be attributed to the fact that information on these measures is the most readily available as opposed to modern management accounting techniques.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Phadoongsitthi (2003) in Thailand supported the view by Joshi (2001) by stating that the reasons for such similarities of low adoption of newly developed management accounting practices between Thai and India is because both countries have cultural similarities like large power distance and low individualism group and both countries facing similar problems like the lack of training and expertise. Research in developed countries (see, for example, Chenhall & Smith, 1998;Pierce & O'Dea, 1998;Abdel-Kader & Luther, 2006), although reporting an increasing usage of modern management accounting practices, agreed that basic or traditional management accounting practices are still dominant in most firms. It is argued that high acceptance of traditional techniques may be attributed to the fact that information on these measures is the most readily available as opposed to modern management accounting techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Phadoongsitthi (2003) reported this technique at rank 20 th which is relatively low. Meanwhile Abdel-Kader & Luther (2006) in their study among British firm revealed that ABC was ranked 32 out of 38 MAPs.…”
Section: Level 4: Lowest Extent Of Usementioning
confidence: 99%
See 2 more Smart Citations
“…Budgets are central to the process of planning and control which are major activities of management in all organizations [2]. The major objective of budgeting is to keep control of the activities done in an organization by providing a roadmap for future activities and setting a series of goals to be achieved and the means to achieve them [3]. A major aspect of financial management involves providing the financing necessary to support assets financing is classified as either debt financing or equity financing.…”
Section: Introductionmentioning
confidence: 99%